COMPARATIVE EFFICACY OF YOHIMBINE AGAINST PYRIDOSTIGMINE FOR THE TREATMENT OF ORTHOSTATIC HYPOTENSION IN AUTONOMIC FAILURE - Shibao, Cyndya (2010)
Orthostatic hypotension affects patients with autonomic failure producing considerable disability because of pre-syncopal symptoms. Severely affected patients may have residual sympathetic tone that can be engaged to increase blood pressure with the alpha-2 adrenergic antagonist yohimbine. This medication activates sympathetic outflow centrally and unrestrains norepinephrine release from noradrenergic neurons. Alternatively, the acetylcholinesterase inhibitor, pyridostigmine, can increase sympathetic tone by improving ganglionic cholinergic neurotransmission. Our purpose was to compare these complementary approaches and test the hypothesis that the combination would lead to synergistic increases in blood pressure. We compared the effects of pyridostigmine 60 mg and yohimbine 5.4 mg in a single-blind, randomized, placebo-controlled, crossover fashion. In a subset of patients we tested the combination of pyridostigmine and yohimbine. Our primary outcome was the change in standing diastolic blood pressure 60 minutes after drug administration from baseline. We studied a total of 31 patients with confirmed severe autonomic failure. Yohimbine significantly improved standing diastolic blood pressure as compared to placebo (11±3 mm Hg 95%CI: 6 to 16, P <0.001). On the contrary, Pyridostigmine did not increase the standing diastolic blood pressure (0.6±3 mm Hg 95%CI: −5 to 5, P =0.823). Only yohimbine showed a significant improvement in presyncopal symptoms. Sixteen patients received the combination of pyridostigmine and yohimbine, but no evidence of synergistic pressor effect was found. Engaging residual sympathetic tone with yohimbine is a more effective approach to improve orthostatic hypotension as compared to pyridostigmine in patients with severe orthostatic hypotension.